P-126 Capturing spiritual care needs in a day therapy unit and in-patient unit setting – using the hope tool. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Salt, Susan; Quinn, Ruth; Baxter, Ian
Abstract : A key element of palliative care is identifying and providing appropriate support for the spiritual care needs of patients. Engaging staff in the process is known to be difficult. A review of chaplaincy service provision in one hospice led to the introduction of a new spiritual care assessment tool based on the HOPE assessment tool. This was done in conjunction with staff attending a day longhealth economy wide training session on the use of the HOPE assessment tool. An audit of the tool was then carried out six months later across the organisation to assess how well it was being used. Over three months the notes of all patients admitted to the adult in-patient unit (IPU) and Day therapy Unit (DTU) were looked at to see if the tool had been completed. Results: The tool was well completed by the DTU and less well by IPU. The tool resulted in 6 formal referrals to the Chaplaincy service, but also generated a number of less formal contacts (personal) communication). Feedback from staff was that the tool was easy to use and well received by patients. There was lack of clarity when to use it, especially on the in-patient unit where staff felt physical symptoms took priority. Further training is taking place and barriers to use of the tool on the in-patient unit are being explored as part of the audit cycle. A further audit of the tools use will be conducted in another 12 months.